Effects of Stress on the Household Development, Kyanamira Subcounty, Kabale District - Blessing Ankunda (Uganda Christian University, 2025)
Abstract This study explored the effects of stress on household development in Kyanamira Subcounty, Kabale District. It was guided by three main objectives: to identify the causes of stress within households, examine how stress affects household development, and propose strategies to reduce stress and promote family well-being. A descriptive survey design was used, combining both qualitative and quantitative approaches to gain a well-rounded understanding of the issue. The research involved 99 participants, including household members, local leaders, community development officers, and health workers, who provided data through structured questionnaires and interviews.The study's descriptive survey approach allows for the collection of both qualitative and quantitative data. To ensure that all groups were fairly represented, stratified random sampling was employed. Focus groups, key informant interviews, and structured questionnaires were used to collect data. While qualitative data was thematically investigated to reveal deeper patterns and insights linked to household stress and development, quantitative data was analysed using descriptive statistics such as frequencies and percentages. The results showed that households are impacted by a number of stressors. One of the main causes was financial instability, which made it hard for families to pay for necessities like food, medical care, and education. Family disputes (such domestic abuse and marital problems), pressure from the workplace, particularly for breadwinners, and health problems including chronic disease and incapacity were additional stressors. Household members' stress levels were also observed to rise in response to peer pressure, societal expectations, and the demands of modern living. It has been demonstrated that stress has a broad impact on household development. People who were under stress found it difficult to concentrate and work efficiently, which resulted in lower income levels and decreased economic production. There were also more incidences of anxiety, depression, high blood pressure, and related disorders, which had a negative impact on mental and physical health. Family ties were upset by prolonged stress, which frequently resulted in divorce, neglect, and bad parenting. Additionally, it resulted in poor financial decision-making, which had an adverse effect on financial planning, savings, and investments. Stress in the family was linked to children's low academic performance and difficulties focusing. The study suggested a number of stress-reduction techniques to deal with these issues. These included providing community-based guidance and counselling services via peer support groups and experts. To increase household income, the government and non-governmental organizations were urged to support economic empowerment initiatives such as financial literacy, income-generating activities, and vocational training. The study also underlined how crucial it is to improve family ties through dispute resolution techniques, parenting classes, and open communication. It was believed that raising awareness of mental health issues through community initiatives was essential to assisting people in recognising and better managing stress. The creation and execution of supportive policies by local governments, such as workplace mental health programs, accessible and reasonably priced healthcare, and community wellness programs, were among the other recommendations. Parents and students were encouraged to learn stress management techniques in schools. In order to lessen the financial strains that lead to stress, broader economic activities like job creation and better credit availability were also considered essential. According to the study, creative stress-reduction techniques catered to the unique circumstances of rural areas should be the focus of future research. The study concluded that stress significantly affects health, productivity, relationships, and education in Kyanamira Sub County, which in turn affects household development. In order to successfully address stress-related issues and advance long-term, sustainable development, it advocated for a cooperative, multi-sectorial strategy involving legislators, community leaders, non-governmental organizations, and households themselves.